Strength in numbers: patient experiences of group exercise within hospice palliative care. Issue 1 (December 2016) - Malcolm, Lorna; Mein, Gill; Jones, Alison; Talbot-Rice, Helena; Maddocks, Matthew; Bristowe, Katherine
Abstract Background Exercise is increasingly recognized as a core component of palliative rehabilitation. The group exercise model is often adopted as a means of reaching more patients with limited resource. Despite the growth of quantitative research examining this area of practice, few qualitative studies have looked at the patient experience of participating in group exercise in a palliative setting, and most exclude patients with a non-cancer diagnosis. Methods The aim of this study was to explore patients' experiences of participating in group exercise classes in a hospice setting. In this qualitative, phenomenological study, nine patients participating in a group exercise programme at a South London hospice completed semi-structured interviews. Participants were purposively sampled by gender, age, ethnicity and diagnosis; to include diagnoses across cancer, respiratory and neurological conditions. Transcripts were interpreted using thematic analysis. Results All patients reported positive experiences of participating in group exercise classes. Improvements reported in physical function had a positive effect on ability to complete activities of daily living and enhanced patient mood. Other reported psychosocial benefits included: promotion of self-management; space and opportunity for reflection; supportive relationships; sharing of information; and a deeper appreciation of patients' own abilities. Conclusion This study highlights the positive experiences and value of group exercise classes to groups of people with diverse cancer and non-cancer conditions. The physical, emotional and psychosocial benefits suggest hospices and other palliative services should explore similar programmes as part of their rehabilitation services. The recognition that exercise groups can be mixed and need not be bespoke to one condition has positive cost and staff resource ramifications.